Students’ Perception of Organization Culture at a Faculty of Science and Technology (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2017)
The current study uses an adapted version of Cameron and Quinn‟s OCAI questionnaire to test the organisational culture of the Faculty of Science and Technology at the University of Debrecen, Hungary, as it is perceived by its students, and also to discover what type of organisational culture the same students think would be ideal for them. An additional objective of this paper is to identify possible gaps between the perceived and the ideal cultures expressed by the students. Our sample includes 128 questionnaires completed by bachelor students from 6 different majors at the faculty. According to our results, the respondents perceive to a significant degree that the faculty‟s organisational culture is at an average level of clan, market and hierarchy cultures, while it also exhibits a relatively low level of the adhocracy culture. Their ideal faculty culture would be one with average adhocracy, average hierarchy, high clan and low market features. Significant gaps are identified between the perceived and ideal cultures in all the four types: students would prefer an increase in clan and adhocracy cultures, and a decrease in the other two cultures.